2007
DOI: 10.1146/annurev.neuro.30.051606.094306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of Smell and Taste inDrosophila

Abstract: The chemical senses-smell and taste-allow animals to evaluate and distinguish valuable food resources from dangerous substances in the environment. The central mechanisms by which the brain recognizes and discriminates attractive and repulsive odorants and tastants, and makes behavioral decisions accordingly, are not well understood in any organism. Recent molecular and neuroanatomical advances in Drosophila have produced a nearly complete picture of the peripheral neuroanatomy and function of smell and taste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
826
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 800 publications
(840 citation statements)
references
References 141 publications
11
826
1
2
Order By: Relevance
“…The TOG contains numerous gustatory receptors, and the DOG contains the olfactory receptors ( Fig. 3A) (20). One report suggested that the TOG contributes to cool avoidance based on calcium imaging with GCaMP and synaptic inactivation of neurons by using the GH86 promoter (13).…”
Section: Resultsmentioning
confidence: 99%
“…The TOG contains numerous gustatory receptors, and the DOG contains the olfactory receptors ( Fig. 3A) (20). One report suggested that the TOG contributes to cool avoidance based on calcium imaging with GCaMP and synaptic inactivation of neurons by using the GH86 promoter (13).…”
Section: Resultsmentioning
confidence: 99%
“…gambiae labellum harbours multiple functional types of ORNs, each expressing a different AgOR in addition to AgOR7, and this ensemble of ORNs expressing a combinatorial of over 20 AgORs converge on one or two medial glomeruli in the antennal lobe. This type of organisation represent a significant departure from established paradigms in the olfactory or gustatory system in insects where ORNs or gustatory receptor neurons (GRNs) with different receptor profiles will converge onto distinct regions of the antennal lobe or the suboesophageal ganglion Zwiebel 2005, Vosshall andStocker 2007).…”
Section: Gambiae Exhibits Olfactory Responses Schematic Dorsal View mentioning
confidence: 95%
“…Recent insights into the molecular and functional mechanisms of sensory perception in Drosophila have been achieved by the use of single-sensillum recordings of adult taste or olfactory sensilla 1,4,[8][9][10][11][12][13] . This method enables sensitive measurements of action potential patterns and shows whether responses are excitatory or inhibitory, but drawing final conclusions about the individual firing neuron is difficult, as each sensillum contains two to four neurons 14 . In the larva, multicellular electrophysiological measurements of the taste system have been performed, but this method is technically challenging and it is not clear how many taste neurons are housed in which sensillum 15 .…”
Section: Introductionmentioning
confidence: 99%